Trauma, Temperament, Alexithymia, and Dissociation Among Persons Addicted to Alcohol: Mediation Model of Dependencies - Zdankiewicz-Ścigała, Elżbieta; Ścigała, Dawid K. (Frontiers in Psychology, 2018)
Objective: The purpose of the study was to examine a model, in which a relation was analyzed between trauma, temperament, alexithymia, and dissociation in a group of individuals addicted to alcohol. Method: The total number of 201 persons were examined, comprising 67 women (33.3% of participants) and 134 men (66.7% of participants). The participants aged from 18 to 68 (M=32.81; SD=12.12). In order to measure the analyzed variables, the following questionnaires were applied: MAST, SSSV, TAS20, TEC, and CES. Results: A comparative analysis between the group of alcohol addicts and non-addicts showed statistically significant differences related to: the intensity of trauma, temperament, alexithymia, and dissociation. The study of models related to the impact of traumatic experience intensity on the level of alcohol addiction with regard to a mediatory role of alexithymia, dissociation, and temperament showed the existence of several important indirect effects, and the model, which takes into account all three mediators, is statistically significant F(4.196)=35.1964; p<0.001. Conclusions: Childhood trauma, as well as alexithymia and dissociation block dealing with stress based on self-reflection and self-control, and contribute to affective disorders and their regulation with alcohol.